Hypothalamic endoplasmic reticulum stress drives pubertal precocity due to early-onset obesity in female rodents - Elvira Rodríguez-Vázquez; Álvaro Aranda-Torrecillas; Manuel Jiménez-Puyer; Oscar Freire-Agulleiro; María J. Sánchez-Tapia; Miguel Ruiz-Cruz; Violeta Heras; María López-Sancho; Luisina Ongaro; Cecilia Perdices-López; Daniel J. Bernard; Rafael Pineda; et al. (Proceedings of the National Academy of Sciences, 2026)
Early-onset obesity, especially in girls, is frequently associated with advanced puberty; a phenomenon bound to increased risk of long-term complications. Hypothalamic endoplasmic reticulum (ER) stress has been implicated in the pathophysiology of obesity and its comorbidities. However, its contribution to pubertal disorders associated with obesity remains unexplored. We report herein that central ER stress drives obesity-induced precocious female puberty. Hypothalamic expression of key ER stress markers was blunted during normal pubertal transition and altered in female rats with early-onset obesity and advanced puberty, which displayed increased levels of p-PERK and p-eIF2α, and reduced ATF6α content. Central stimulation of hypothalamic ER stress with Thapsigargin in prepuberal lean female rats mimicked advanced puberty onset caused by obesity, without changes in body weight. This phenomenon seemingly involves a circuit including the hypothalamic arcuate nucleus (ARC), since obesity-induced precocious puberty was largely prevented by alleviation of ER stress via virogenetic overexpression of the ER chaperone, GRP78, in the ARC, but not in the paraventricular nucleus, in female rats. In addition, expression analyses of ER stress markers in mouse Kiss1 neurons isolated from juvenile and pubertal female mice revealed increased expression of Perk and Ire1α mRNAs in Kiss1 ARC neurons in early-overfed mice at the juvenile stage, while Xbp1s/u expression ratio was significantly increased during juvenile–pubertal transition in overweighed mice. Collectively, our data uncover a relevant role of hypothalamic ER stress in the control of female puberty and the pathogenesis of obesity-induced pubertal alterations.